1970
DOI: 10.1111/j.1365-2133.1970.tb06094.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand Dermatitis in Housewives

Abstract: SUMMARY.— In a series of 4000 patients patch tested in 5 European clinics, 1000 were engaged in domestic work only; they included 281 women with contact dermatitis of the hands. There were no significant differences between the 2 groups as regards age, duration of dermatitis and patch test results. Half of the 281 women had a positive patch test, the responsible allergens in order of rank being balsams, nickel, medicaments, cobalt, rubber, chromate, benzocaine and paraphenylenediamine. But 78% of them were dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
3
2

Year Published

1971
1971
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 0 publications
2
10
3
2
Order By: Relevance
“…7 Also, Calnan et al found majority (42%) patients of hand dermatitis occurred between 20-39 years. 8 This may be because the capacity for sensitization is less in extremes of age and also may be due to the decreased occupational exposure to various allergens.…”
Section: Discussionmentioning
confidence: 99%
“…7 Also, Calnan et al found majority (42%) patients of hand dermatitis occurred between 20-39 years. 8 This may be because the capacity for sensitization is less in extremes of age and also may be due to the decreased occupational exposure to various allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Wir stellten in einer ersten Übersichtsarbeit 1986 anhand der damalig aktuellen Literatur und anhand unserer eigenen Daten die häufigsten Kontaktallergene bei Hausfrauen/-männern vor [38]. In 5 unterschiedlichen Kollektiven mit kleinen Fallzahlen wurden insgesamt 48 Allergene als die jeweils 10 häufigsten Allergene bei Patienten mit Hausfrauenekzem ermittelt [1,7,12,18]. Dies kann zum einen durch die zu kleinen Kollektive erklärt werden, zum anderen auch durch regionale Unterschiede von z.B.…”
Section: Methoden Kollektivunclassified
“…Der Altersschwerpunkt liegt somit höher als in anderen Studien, die den Häufigkeits-gipfel des Hausfrauenekzems eher zwischen dem 20. und 50. Lebensjahr angesiedelt sahen [1,7,12] …”
Section: Introductionunclassified
“…During the years between 1948 and 1987, the frequency of contact dermatitis was determined with large collectives (on average 1517 persons) in various countries by means of patch tests (1 % or 2 % p-phenylenediamine in vaseline). On average and independent of sex or race, positive reactions were seen in 9 % of the tested persons [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Allergenic Effectsmentioning
confidence: 99%